Deteksi Dini Perilaku Prososial pada Remaja dan Intervensi Bimbingan dan Konseling - Nur Annisa Sawitri; Juwita Madira; Ghina Rizki Amalia; Saniya Putri Ayu Febiolantika; Rizki Novirson; Resti Okta Sari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Prosocial behavior is an important aspect of adolescents’ social-emotional development that needs to be optimally fostered through early detection efforts to prevent the emergence of social and mental health problems. This study employed a library research method by reviewing various journals and scientific articles related to the early detection of adolescent prosocial behavior. The findings indicate that prosocial behavior is influenced by internal factors such as empathy, emotional regulation, emotional intelligence, self-concept, and religiosity, as well as external factors including family environment, peer relationships, and education. Early detection enables school counselors to design intervention services that are aligned with students’ developmental needs. Therefore, it is essential to implement Guidance and Counseling services through the teaching of prosocial skills, empathy, communication, emotional regulation, conflict resolution training, and the enhancement of students’ self-efficacy. The use of social media to reinforce positive behavior, the provision of positive communication modules, and collaboration among teachers, parents, and the entire school community serve as systematic and sustainable strategies in shaping adolescents’ prosocial character.